American Gods : my Ainsel - Gaiman, Neil; Russell, P. Craig (Gaiman, Neil. American gods., 2019)
"Shadow and Wednesday leave the House on the Rock and continue their journey across the country where they set up aliases, meet new gods, and prepare for war."--